2019
DOI: 10.1177/2309499019874470
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of edaravone on systemic inflammation and local damage in skeletal muscles following long-term ischemia to murine hind limb

Abstract: Purpose: The purpose of this study was to evaluate local and systemic pathology in a murine model of ischemia–reperfusion (I/R) injury induced by long-term application of a tourniquet on the hind limbs and to assess the protective effects of edaravone, a potent systemic scavenger of free radicals, using this model. Methods: Sixty C57BL6 mice were divided in two groups, with one group receiving a 3 mg/kg intraperitoneal injection of edaravone and the other group receiving an identical amount of saline 30 min be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…[ 55 ] ED supplementation suppressed TLR‐4/NF‐κB signaling, TNF‐ α , and IL‐6 and increased IL‐10 and iKK β in the urinary bladder of CP‐intoxicated rats, demonstrating a potent anti‐inflammatory activity. Accordingly, numerous studies showed that the protective effect of ED against liver, [ 56 ] lung, [ 57 ] and skeletal muscle [ 58 ] injuries were associated with the inhibition of NF‐κB. This inhibitory activity of ED was further explored using molecular docking simulation, which showed its ability to bind to TLR‐4 and NF‐κB.…”
Section: Discussionmentioning
confidence: 99%
“…[ 55 ] ED supplementation suppressed TLR‐4/NF‐κB signaling, TNF‐ α , and IL‐6 and increased IL‐10 and iKK β in the urinary bladder of CP‐intoxicated rats, demonstrating a potent anti‐inflammatory activity. Accordingly, numerous studies showed that the protective effect of ED against liver, [ 56 ] lung, [ 57 ] and skeletal muscle [ 58 ] injuries were associated with the inhibition of NF‐κB. This inhibitory activity of ED was further explored using molecular docking simulation, which showed its ability to bind to TLR‐4 and NF‐κB.…”
Section: Discussionmentioning
confidence: 99%
“…The HO-1, NQO1 and SOD are protective proteins against oxidative stress, and MDA is a common product of oxidative stress. 37,38 HO-1 functions as an important protein of cell adaptation to oxidative stress by generating carbon monoxide, biliverdin and free iron. 39 NQO1 is a type of cytosolic flavoprotein, which can transfer electrons, 40 hydroquinones.…”
Section: Discussionmentioning
confidence: 99%
“…29) On the other hand, the intestinal mucosal barrier injury caused by AP can cause intestinal conditions pathogenic bacteria to shift into the blood circulation, and the resulting exogenous ligands are recognized by TLR4, start the NFκB pathway, and up-regulate the expressions of inflammatory mediators such as cytokines and chemokines. 30) Some studies show that the protective effect of edaravone against acute lung injury, 31) skeletal muscles, 32) acute kidney injury 33) and acute stroke 34) associated with the NFκB activation and inflammatory cytokine production. In addition, other studies point to EDA inhibition of mRNA levels of TLR4 and NFκB expression in cerebral ischemia-reperfusion in mice.…”
Section: Discussionmentioning
confidence: 99%